Global value chain participation and exchange rate pass-through - Georgios Georgiadis; Johannes Gräb; Makram Khalil (Deutsche Bundesbank, 2020)
This paper draws a causal link between the rise of global value chain participation (GVCP) and the decline of exchange rate pass-through (ERPT) to import prices over the last decades. We first illustrate in a structural two-country model how greater GVCP can reduce ERPT to import prices. In the model, the sensitivity of an economy's home-currency production costs to exchange rate changes rises as it exhibits greater GVCP by importing a larger share of its intermediate inputs. The increased sensitivity of the economy's home-currency production costs to exchange rate changes translates into a higher sensitivity of its home-currency export prices. The latter implies a reduction of the sensitivity of the economy's foreign-currency export prices - i.e. its trading partner's home-currency import prices - to exchange rate changes. Hence, an increase in the economy's GVCP implies a fall in its trading partner's ERPT to import prices. We then estimate instrumental variable regressions using adopted trade agreements as instruments for economies' GVCP in a cross-country panel dataset for the time period from 1995 to 2014. Consistent with the mechanism spelled out in the theoretical model, we find that ERPT to export prices has been higher in economies which exhibit greater GVCP, and that ERPT to import prices has been lower in economies whose trading partners exhibit greater GVCP.
Keywords: F32; F41; F62; 330; global value chain participation; exchange rate pass-through